A prospective study of the accuracy of Doppler ultrasound in detecting carotid artery disease. Issue 8 (August 1981) - Lakeman, M J; Sherriff, S B; Martin, T R
Abstract : Results are presented from a two year prospective study using a Doppler ultrasound technique for the detection of carotid disease. The patients studied presented with transient cerebral ischaemic attacks or small strokes in the carotid territory. No other form of patient selection was used. Results were compared with those from carotid and arch aortography. 86% of normal vessels and 78% of diseases vessels were correctly classified. It is concluded that this technique offers a safe and accurate screening procedure for the management of patients presenting with transient cerebral ischaemia or small strokes.